2021
DOI: 10.1038/s41467-020-20282-1
|View full text |Cite
|
Sign up to set email alerts
|

ZNF143 mediates CTCF-bound promoter–enhancer loops required for murine hematopoietic stem and progenitor cell function

Abstract: CCCTC binding factor (CTCF) is an important factor in the maintenance of chromatin–chromatin interactions, yet the mechanism regulating its binding to chromatin is unknown. We demonstrate that zinc finger protein 143 (ZNF143) is a key regulator for CTCF-bound promoter–enhancer loops. In the murine genome, a large percentage of CTCF and ZNF143 DNA binding motifs are distributed 37 bp apart in the convergent orientation. Furthermore, deletion of ZNF143 leads to loss of CTCF binding on promoter and enhancer regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
59
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(65 citation statements)
references
References 66 publications
6
59
0
Order By: Relevance
“…Of note, changes in chromatin accessibility regulates transcription of ALKBH5 , an important m 6 A demethylase required for maintaining leukemia stem cells (LSCs) function 72 . Due to the fact that chromatin status, such as histone modifications and chromatin interactions, plays important role in hematopoiesis 73,74 , another aspect to consider is that the regulation of ADAR2 expression through dynamic changes of chromatin status. In sum, our findings shed new light on future studies of dysregulated ADAR2 transcription and expression as well as their RNA editing-dependent or independent biological implications in multiple diseases including cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, changes in chromatin accessibility regulates transcription of ALKBH5 , an important m 6 A demethylase required for maintaining leukemia stem cells (LSCs) function 72 . Due to the fact that chromatin status, such as histone modifications and chromatin interactions, plays important role in hematopoiesis 73,74 , another aspect to consider is that the regulation of ADAR2 expression through dynamic changes of chromatin status. In sum, our findings shed new light on future studies of dysregulated ADAR2 transcription and expression as well as their RNA editing-dependent or independent biological implications in multiple diseases including cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, ZNF143 binds to promoters globally [367] and was found at the anchors of many lineage-specific enhancer-promoter loops in human and mouse cells [362][363][364]368]. Unlike CTCF and cohesin, long-term depletion of YY1 or ZNF143 in mammalian cells causes a significant reduction of enhancer-promoter loops, coupled with substantial changes in gene expression [295,368,369] (although short-term YY1 depletion has only a modest effect on both [350]).…”
Section: Yy1 and Znf143mentioning
confidence: 99%
“…YY1 does not seem to co-localise with CTCF [365] and instead has been proposed to associate with cohesin independently, in a manner analogous to CTCF itself [295]. In contrast, ZNF143 co-localises with both CTCF and cohesin [369], and it has recently been shown that depletion of ZNF143 disrupts CTCF-mediated enhancer-promoter looping [368].…”
Section: Yy1 and Znf143mentioning
confidence: 99%
“…While TEAD4 is known to contribute to drive embryonic cell commitment to blood cells 46 , GATA1, HIF1A and epigenetic enzymes SETB1, EZH2 and HDAC2 regulate HSCs self-renewal and/or differentiation 4751 . Instead, ZNF143 and SMC3 bind to anchors of chromatin interactions to regulate the three-dimensional genome organisation, in collaboration with CTCF 38,52,53 . ZNF143 and SMC3 cistromes enrich over LTR41B elements with CTCF and known CTCF interactors (SMC1A, RAD21, CHD8 (q≤3.22e-34, OR≤9.36) (Suppl.…”
Section: Resultsmentioning
confidence: 99%